Islamic Psychological Employability: The Role of Self-Confidence in Pesantren-Based Vocational Schools - M. Syukron Maksum; Martinis Yamin; Kasful Anwar Us; Sodiah Sodiah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Employability has become an essential outcome of vocational education, requiring not only technical competence but also strong psychological readiness among students. This study aimed to examine the direct and indirect effects of self-esteem, self-efficacy, and self-confidence on employability among students in pesantren-based vocational schools. Using a quantitative survey design, data were collected from 80 students enrolled in three pesantren-based vocational schools through a Likert-scale questionnaire and analyzed using path analysis. The findings revealed that self-confidence had the strongest direct effect on employability (R² = 81.8%), while self-esteem and self-efficacy demonstrated relatively weak direct effects. However, both variables showed stronger indirect effects through self-confidence, with mediation effects of 33.5% and 17.3%, respectively. The study contributes to employability research by highlighting self-confidence as a central psychological mechanism linking psychological resources to work readiness and proposes the Islamic Psychological Employability (ISPE) Model. The findings recommend integrating confidence-building programs into vocational education to strengthen graduates' employability.